Lung cancer molecular epidemiology in China: recent trends - Zhou, Caicun (Translational Lung Cancer Research; Vol 3, No 5 (October 21, 2014): Translational Lung Cancer Research [The 14th Central European Lung Cancer Congress (CELCC)], 2014)
Lung cancer is both the most common diagnosed cancer and the leading cause of cancer related deaths in China. During the past three decades, the incidence and mortality of lung cancer in China are increasing rapidly. According to data from National Central Cancer Registry (NCCR) in 2010, the crude incidence of lung cancer in China was 46.08 per 100,000 population (61.86 per 100,000 men and 29.54 per 100,000 women), with an estimated over 600,000 new diagnosed lung cancer patients (416,333 males and 189,613 females). Meanwhile, the crude mortality of lung cancer in China was 37.00 per 100,000 population (50.04 per 100,000 men and 23.33 per 100,000 women). Consistent with the change in developed countries, adenocarcinoma has become the most predominant histological subtype of lung cancer in China. For the majority advanced non-small-cell lung cancer (NSCLC) patients, especially patients with adenocarcinoma, targeted therapy became increasing important in the treatment. Chinese researcher have done a lot work in terms of lung cancer molecular epidemiology, therefore, in this review, we further summarized the epidemiology of driver genes in NSCLC, hoping to help clinicians to better screen certain driver genes in China for treatment decisions.